Advances in agronomy. - Sparks, Donald L., 1953- (Advances in agronomy ;, 2002)
This volume in Advances in Agronomy contains seven outstanding reviews that discuss cutting edge developments in the crop and soil sciences. Chapter 1 addresses desertification and its relation to climate change. Chapter 2 discusses fate and transport of viruses in porous media. Chapter 3 is a comprehensive treatment of the future needs of root water and nutrient uptake modeling. Chapter 4 is a review on micronutrients in crop production, including a discussion on improving the supply and acquisition. Chapter 5 provides information on soils in tropical and temperate regions. Chapter 6 desribe.